RATIONAL MANAGEMENT OF PARKINSON’S DISEASE - Mun Yin Yen; Ketut Tirtayasa; Dewa Putu Sutjana (Bali Journal of Medical and Health Sciences, 2013)
Parkinson’s disease is a chronic and progressive neurodegenerative disease which is characterized by motor and non-motor symptoms. The motor symptoms which are also known as cardinal features are resting tremor, bradykinesia, rigidity and postural instability. The etiology is unknown in most cases but there are findings that relate Parkinson’s disease to the genetics and environmental factors. The clinical course of Parkinson’s disease varies from patient to patient. Levodopa is still the main therapy of this disease although it leads to motor complications as the disease progresses.